2017
DOI: 10.1039/c7ra00075h
|View full text |Cite
|
Sign up to set email alerts
|

Surface active ionic liquid induced conformational transition in aqueous medium of hemoglobin

Abstract: The molecular interactions and effect of SAILs on the conformation of human hemoglobin (Hb) has been studied using various techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 62 publications
1
16
1
Order By: Relevance
“…After C 1 with increasing amount of [C 6 mim][C 12 OSO 3 ] the hydrophobic interactions between [C 6 mim][C 12 OSO 3 ] and TC were dominated over the hydrogen bonding between solvent molecules and the ground state which reduces energy gap and decreases intensity with red shift of maximum intensity ( λ 305.5 ). The intensity continues to decrease till cmc reached due to the increase in the amount of solubilized CPZ in micelles . These changes in band II of CPZ also confirm the complex formation between CPZ and [C 6 mim][C 12 OSO 3 ] favored by various interacting forces such as strong electrostatic interactions, hydrogen bonding, hydrophobic interactions and π‐π stacking interactions.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…After C 1 with increasing amount of [C 6 mim][C 12 OSO 3 ] the hydrophobic interactions between [C 6 mim][C 12 OSO 3 ] and TC were dominated over the hydrogen bonding between solvent molecules and the ground state which reduces energy gap and decreases intensity with red shift of maximum intensity ( λ 305.5 ). The intensity continues to decrease till cmc reached due to the increase in the amount of solubilized CPZ in micelles . These changes in band II of CPZ also confirm the complex formation between CPZ and [C 6 mim][C 12 OSO 3 ] favored by various interacting forces such as strong electrostatic interactions, hydrogen bonding, hydrophobic interactions and π‐π stacking interactions.…”
Section: Resultsmentioning
confidence: 56%
“…The intensity continues to decrease till cmc reached due to the increase in the amount of solubilized CPZ in micelles. [47] These changes in band II of CPZ also confirm the complex formation between CPZ and [C 6 mim][C 12 OSO 3 ] favored by various interacting forces such as strong electrostatic interactions, hydrogen bonding, hydrophobic interactions and p-p stacking interactions.…”
Section: Uv-visible Spectroscopymentioning
confidence: 52%
“…S3‐S5). The results of investigations revealed that both compounds 12 b and 13 c showed appreciable K a = 13.08 and 19.71 × 10 3 m −1 (Table S1), respectively, which indicates that 13 c ‐[DHPS] binding is stronger than 12 b ‐[DHPS].…”
Section: Resultsmentioning
confidence: 99%
“…The IFT values between the crude oil and DIW containing different type of ILs at their CMC are given in Table . A wide range of CMC values from 7 mM to 16.8 mM have been previously reported in the literature for IL12, which is strongly dependent on the desired parameters including IFT, electrical conductivity (EC), H NMR spectroscopy, fluorescence, EMF and surface tension. Consequently, it is necessary to determine the CMC value for each specific system and for a specific desired parameter. In this study, the CMC value for IL12 was about 4000 ppm (∼13.94 mM) in DIW, based on the IFT parameter.…”
Section: Results and Discussionmentioning
confidence: 99%